2017
DOI: 10.5267/j.esm.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Some recent criteria for brittle fracture assessment under mode II loading

Abstract: Different criteria are available in the literature to assess the fracture behaviour of sharp Vnotches. A typical and well-known criterion is based on the application of the notch stress intensity factors (NSIFs), which are able to quantify the intensity of the stress fields ahead of the notch tip. This work considers two recent energy-based criteria applied here to sharp Vnotches. The first criterion is based on the averaged value of the strain energy density (SED), while the second one called Finite Fracture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The rock specimen for K Ic measurements usually has either a straight‐through notch or a chevron notch. The straight‐through notch is often regarded as the critical crack whose length is directly correlated to the fracture toughness calculation, so the notch tip must be machined to be very sharp, as the local stresses/strains/energies ahead of a blunt notch tip are quite different from those ahead of a crack tip . Otherwise, costly precracking procedures are needed for the straight‐notch specimens to generate a crack.…”
Section: Introductionmentioning
confidence: 99%
“…The rock specimen for K Ic measurements usually has either a straight‐through notch or a chevron notch. The straight‐through notch is often regarded as the critical crack whose length is directly correlated to the fracture toughness calculation, so the notch tip must be machined to be very sharp, as the local stresses/strains/energies ahead of a blunt notch tip are quite different from those ahead of a crack tip . Otherwise, costly precracking procedures are needed for the straight‐notch specimens to generate a crack.…”
Section: Introductionmentioning
confidence: 99%
“…However some other researchers have demonstrated that by considering more precise description for the crack tip stress/strain field, more accurate theoretical predictions can be obtained for combined mode fracture of brittle materials . For instance, taking into account the influence of first nonsingular stress term (often called T ‐stress) in addition to K I and K II via the generalized MTS criterion proposed first by Smith et al can reduce significantly the difference between the test data and theoretical predictions of combined mode I + II fracture in several engineering brittle materials . The practical ability of such theoretical frameworks has rarely been investigated till now for crack growth behaviour of aged and unaged bitumen and binder.…”
Section: Resultsmentioning
confidence: 99%
“…[65][66][67][68] For instance, taking into account the influence of first nonsingular stress term (often called T-stress) in addition to K I and K II via the generalized MTS criterion proposed first by Smith et al 65 can reduce significantly the difference between the test data and theoretical predictions of combined mode I + II fracture in several engineering brittle materials. [69][70][71][72][73][74][75] The practical ability of such theoretical frameworks has rarely been investigated till now for crack growth behaviour of aged and unaged bitumen and binder. Hence in the following, the ability of conventional and generalized MTS criteria are examined for predicting the combined mode I + II fracture toughness data obtained for the aged and unaged 30/40 bitumen.…”
Section: Specimen Manufacturing and Testingmentioning
confidence: 99%
“…In spite of significant progress in the study of the effect of welding residual stress on the fatigue crack growth rate, the interpretation of most results is given in terms of the stress intensity factor in the framework of the validity of linear elastic fracture mechanics. It should be noted that other failure theories such strain‐based criteria can also be used to predict the fatigue life of welded structures …”
Section: Introductionmentioning
confidence: 99%